Affording states a margin of appreciation: comparing the European Court of Human rights and the Inter-American Court of Human Rights - McGoldrick, Dominic (Brill, 2016)
We live in an era of proliferating international legal domains and institutions, not least in the human rights field. For some, normative pluralism within human rights is inevitable, and even desirable. Others view it as a threat to the integrity and coherence of international human rights protection. How far do human rights standards and their interpretation by different regional and international human rights systems diverge? To what extent do human rights bodies ‘borrow’ from or influence each other in respect of their case law, practices and procedures? Is global human rights protection fragmenting or heading towards greater coherence? This edited collection addresses these questions through the insights of leading scholars and jurists with first-hand experience of human rights adjudication and litigation.